Information and Communication Technology Teachers' Competence to Support Learning Activities at Elementary School - Elvariani, Elvariani; Abdurrahman, Abdurrahman; Siraj, Siraj (Universitas Pahlawan Tuanku Tambusai, 2025)
Technological developments in the digital era affect many aspects of life, including education. The use of Information and Communication Technology (ICT) is very important in learning in schools, so teachers' ICT competence needs to be considered. This research aims to understand the ICT competency of teachers in Elementary Schools in Lawe Bulan District, Southeast Aceh Regency, efforts to improve this competency, and the factors that influence teacher ICT capabilities. This research uses qualitative methods with interviews, observation and documentation. The research subjects consisted of 76 teachers, with observations on 6 teachers selected based on certain criteria. The average teacher ICT competency in Elementary Schools in Lawe Bulan District is 61 respondents, and 58 respondents are in the